2014
DOI: 10.1073/pnas.1322258111
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and ultrastructural features of human induced pluripotent and embryonic stem cell-derived skeletal myocytes in vitro

Abstract: Progress has recently been made toward the production of human skeletal muscle cells from induced pluripotent stem (iPS) cells. However, the functional and ultrastructural characterization, which is crucial for disease modeling and drug discovery, remains to be documented. We show, for the first time to our knowledge, that the electrophysiological properties of human iPS-derived skeletal myocytes are strictly similar to those of their embryonic stem (ES) cell counterparts, and both are typical of aneural mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 45 publications
7
50
0
Order By: Relevance
“…While these studies are encouraging, ultrastructural analyses have shown that hPSC-derived myofibers have myofibrils that are less regularly organized than those found in vivo, featuring irregular and misaligned Z-disks. They also fail to form a mature T-tubule network, a hallmark of adult myofibers (Skoglund et al, 2014). Although triad-like structures could be identified, they were limited to the subsarcolemmal space, lacking the orthogonal alignment to myofibrils observed in vivo.…”
Section: Myofiber Maturation In Vitro Sarcomeres and Structural Assemblymentioning
confidence: 96%
See 3 more Smart Citations
“…While these studies are encouraging, ultrastructural analyses have shown that hPSC-derived myofibers have myofibrils that are less regularly organized than those found in vivo, featuring irregular and misaligned Z-disks. They also fail to form a mature T-tubule network, a hallmark of adult myofibers (Skoglund et al, 2014). Although triad-like structures could be identified, they were limited to the subsarcolemmal space, lacking the orthogonal alignment to myofibrils observed in vivo.…”
Section: Myofiber Maturation In Vitro Sarcomeres and Structural Assemblymentioning
confidence: 96%
“…Remarkably, the formation of such long striated myofibers is rarely observed when primary myoblasts, myogenic lines (such as C2C12) or satellite cells are differentiated in vitro, as they tend to form poorly organized multinucleated myosacs. Electron microscopy analysis of mouse and human PSC-derived myofibers revealed that they exhibit highly organized sarcomeric units, reminiscent of the cytoarchitecture found in vivo (Hirsch et al, 1998;Skoglund et al, 2014). Myofibrils generated in these fibers can exhibit the appropriate organization of MyHC, troponin T, nebulin and titin, and undergo the stage-specific developmental transitions through α-actins (cardiac to skeletal) and MyHC (embryonic, fetal, and perinatal/fast) isoforms (Chal et al, 2015;Hirsch et al, 1998;Mizuno et al, 2009;Rohwedel et al, 1998b).…”
Section: Myofiber Maturation In Vitro Sarcomeres and Structural Assemblymentioning
confidence: 97%
See 2 more Smart Citations
“…Second, the generation of hiPSC-derived myoblasts by PAX7 over expression was done as previously described by Darabi and colleagues (Darabi et al, 2012;Skoglund et al, 2014). Details are described in supplemental methods.…”
Section: Differentiation Of Hipsc Into Myoblasts or Motoneuronsmentioning
confidence: 99%